Meso-structural evaluation of asphalt mixture based on pore cellular structure model. Issue 8 (3rd July 2022) - Shi, Liwan; Wang, Duanyi; Lin, Peihong; Sun, Xiaoli; Qin, Xiao
ABSTRACT: To provide a reference for the gradation-refined design of asphalt mixtures, pore cellular structure model was developed to evaluate the meso-structure of asphalt mixture, and corresponding meso-structural evaluation indices of the coarse aggregate main skeleton and asphalt mortar interference were obtained. Then three different asphalt mixtures were selected to study the influence of gradation and asphalt mortar performance on the meso-structure of pore cellular structures. The gradual behaviour characteristics of the meso-evaluation indices subjected to load, as well as the correlation between the main skeleton meso-evaluation indices and macro deformation were studied. The results indicated that gradation is a key determinant of the contact point, number of pore cells, and area of pore cell distribution. Under the action of loads, the number of contact points and pore cells within the asphalt mixture increase, interference coefficient decreases, and skeleton rate increases gradually; coarse aggregates with contact that are not involved in the pore cellular structure are the main factor affecting skeleton rate. Meso-structural evaluation indices including interference coefficient and skeleton rate can effectively evaluate the meso-structure of the asphalt mixture, ensure that the coarse aggregates are interlocked with each other to form a stable main skeleton.